2018
DOI: 10.1038/s41598-017-19100-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-sequencing resolves self-antigen expression during mTEC development

Abstract: The crucial capability of T cells for discrimination between self and non-self peptides is based on negative selection of developing thymocytes by medullary thymic epithelial cells (mTECs). The mTECs purge autoreactive T cells by expression of cell-type specific genes referred to as tissue-restricted antigens (TRAs). Although the autoimmune regulator (AIRE) protein is known to promote the expression of a subset of TRAs, its mechanism of action is still not fully understood. The expression of TRAs that are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 70 publications
10
40
0
Order By: Relevance
“…That being said, we were unable to explain membership to co-expression groups by any of the features we examined, including gene category, chromosome localisation, genomic distance, tissue specificity, autoimmune disease association, and inclusion in a specific biological pathway. The largely random distribution of genes in modules across the genome is in keeping with observations from previous studies (Meredith et al, 2015;Pinto et al, 2013;Miragaia et al, 2018). Our results are also consistent with previously published studies that concluded that PGE patterns in mTEC are dictated neither by expression patterns seen in differentiated peripheral cell types nor by coregulation by specific transcription factors (Meredith et al, 2015;Villaseñor et al, 2008;Pinto et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…That being said, we were unable to explain membership to co-expression groups by any of the features we examined, including gene category, chromosome localisation, genomic distance, tissue specificity, autoimmune disease association, and inclusion in a specific biological pathway. The largely random distribution of genes in modules across the genome is in keeping with observations from previous studies (Meredith et al, 2015;Pinto et al, 2013;Miragaia et al, 2018). Our results are also consistent with previously published studies that concluded that PGE patterns in mTEC are dictated neither by expression patterns seen in differentiated peripheral cell types nor by coregulation by specific transcription factors (Meredith et al, 2015;Villaseñor et al, 2008;Pinto et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Cell-based clustering of our data supports previous observations that the mTEC compartment is heterogeneous (Bornstein et al, 2018;Miragaia et al, 2018), a notion supported by studies tracking TEC differentiation during organogenesis and regeneration (Gäbler et al, 2007;Yano et al, 2008;Wang et al, 2012;Metzger et al, 2013;Nishikawa et al, 2014;Ohigashi et al, 2013;Mayer et al, 2016;Ohigashi et al, 2015). These suggest that mTEC derive during embryogenesis from progenitors expressing claudins-3 and -4 and SSEA-1 (Hamazaki et al, 2007;Sekai et al, 2014), and postnatally from a population localised at the corticomedullary junction expressing podoplanin and CCL21 (Onder et al, 2015;Michel et al, 2017;Mayer et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is because many micro-environmental perturbations and stochastic factors at the cellular level are known to change the scEV. These factors may include local cell density, cell size, shape and rate of proliferation, cell cycle, and so on (Snijder et al 2009;McDavid et al 2014;Kernfeld et al 2018;Miragaia et al 2018;Mitchell et al 2018). To work on the cell-to-cell variability, these confounding factors have to be controlled.…”
Section: Introductionmentioning
confidence: 99%